KONTRIBUSI REGULASI DIRI TERHADAP PENYESUAIAN DIRI REMAJA PUTRI PONPES SUMATERA THAWALIB PARABEK - Zirizkana Zirizkana; Yolivia Irna Aviani (Universitas Negeri Padang, 2019)
This study aims to see the contribution of self-regulation to selfadjustment to teenage girls at the Thawalib Parabek Islamic Boarding School. The design of this study is a quantitative method. The population in this study were female students of class VIII and IX tsanawiyah. The total sample is 180 students. Subject collection using purposive sampling. Data retrieval techniques are processed using questionnaires and using linear regression analysis techniques. Based on the research, the results of the regeresi value were 0,000 (p <0.05). These results indicate that the hypothesis is accepted, which means that there is a contribution of self-regulation to self-adjustment to teenage girl at the Islamic Boarding School in Sumatra Thawalib Parabek with a positive contribution direction.Penelitian ini bertujuan untuk melihat kontribusi regulasi diri terhadap penyesuaian diri pada remaja putri di Pondok Pesantren Sumatera Thawalib Parabek. Desain penelitian ini adalah metode kuantitatif. Populasi dalam penelitian ini adalah santri putri kelas VIII dan IX tingkat tsanawiyah. Jumlah sampel dalam penelitian ini sebanyak 170 santri. Pengambilan subjek menggunakan purposive sampling. Teknik pengambilan data diolah menggunakan angket dan menggunakan teknik analisis regresi linier. Berdasarkan penelitian diperoleh hasil nilai regeresi sebesar 0,000 (p<0,05). Hasil tersebut menunjukkan bahwa hipotesis diterima, yang artinya ada kontribusi regulasi diri terhadap penyesuaian diri pada remaja putri di Pondok Pesantren Sumatera Thawalib Parabek dengan arah kontribusi positif.